Leave Wagner alone. Strategie dramaturgiczne w The Loop of the Nibelung Simona Steena-Andersena - Batog, Iga (Res Facta Nova, 2025)
The article is an attempt to describe the video-installation by Simon Steen-Andersen titled The Loop of the Nibelung. The piece is a continuation of the Run Time Error cycle, combined with a documentary about Norwegian singer Kirsten Flagstad and a fragmentary staging of Richard Wagner’s The Ring of the Nibelung. I analyze the audiovisual strategies used by the composer, especially those related to the relationship between the voice and the body of performers. I have also described the composer's creative process and the site-specific aspect of the installation, and I examined the work in the context of a dialogue with the legacy of Richard Wagner. The issue of authorship and influence between the figures of Steen-Andersen and Wagner has also been addressed.